(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2023)
Whether we discuss poverty from an economic or political standpoint, it has always been a significant concern. A developing nation is mostly assessed based on the programmes it implements to improve the lives of its citizens. One such nation is India, where the MGNREGA programme has been implemented as a significant effort to reduce poverty. Since the programme has been running for a while, we can assess its success based on how individuals have been influenced by it or how they have reacted to it. Given the size of India’s population (which is primarily subsistence-level, as evidenced by the epidemic), we chose to investigate the statistics for West Bengal, a state that is more prosperous. The programme has occasionally served as a cushion and, for some segments of the population, has served as a life support system. According to data, the Act has assisted in reducing poverty, but we must determine if it has also improved the lives and standards of the population or merely stopped their decline and created stagnation. This essay primarily examines whether West Bengal has seen any poverty reduction as a result of MGNREGA. Our perspective is based on data that has been made available to us by a number of sources. The findings supported the assertion that this initiative had helped to reduce poverty. For a country like India, there must be disparity if there is data, albeit it has decreased with time. It is up to the reader’s discretion whether they wish to accept our findings or carry out their own research to obtain a fuller picture.